Evaluating user’s satisfaction of bus service in Mauritius: Decision tree approach - T. Champahom; R. Goodary; R. Beeharry; S. Jomnonkwao; V. Ratanavaraha (International Association of Lowland Technology, 2019)
In Mauritius, travelling by bus service widely plays an important role in people’s transportation. In 2011, there were 220 bus routes for bus transportation, and 900 bus stops. This research aimed to study the satisfaction of bus users with a variety of service kinds divided into four main aspects including Vehicle, Driver behavior, Bus stop facility, and Service. The data used for analysis were obtained from 531 completely screened questionnaires inquiring bus users’ satisfaction in Mauritius. The data were analyzed using Decision tree to classify the importance of criteria for bus users’ satisfaction and the Importance performance analysis was used to identify Items in each quadrant of which the meaning was different. The result obtained for the most important question item will be used to improve bus service in order to serve bus users’ needs. From data analysis, it was found that the strength of bus service in Mauritius was Driver and crew’s customs, and the weaknesses were the frequency of bus service and the locations of bus stop facility. In terms of IPA analysis, the frequency of bus services should increase and the locations of bus stops should be safer.